Pengetahuan Dengan Kemampuan Komunikasi Terapeutik Perawat Pada Pasien Anak Usia Prasekolah (Knowledge and Nurses' Therapeutic Communication Skills in Pre-School Age Patient) - Idayati Idayati; Diny Vellyana; Sondang Sondang (Jurnal Kesehatan, 2020)
AbstractHaving treatment in a hospital (hospitalization) is an unpleasant and threatening experience for everyone, especially for children who are still in the process of growth and development. One way to resolve this problem is to use therapeutic communication effectively which will and will be carried out nursing actions. To communicate with children, special approaches or techniques are needed so that the relationship can run well according to the child's growth and development. One of the predisposing factors according to Lawrencen Green's theory is knowledge, when a nurse has good knowledge, her ability in therapeutic communication will be good too. The aim of study is to determine the relationship of knowledge with the therapeutic communication skills of nurses in pediatric patients. This research uses survey analytic methode with crosssectional. Sample in the study were 66 nurses in inpatient rooms of Graha Husada Hospital,technique purposive samplingfor sampling.Data analysis using the Spearman Rank (Rho) correlation test with a significance level (α = 0.05)  is obtained p value 0.025 (p <0.05). There is relationship of knowledge with therapeutic communication ability of nurses in pediatric patients treated at Graha Husada Hospital  Bandar Lampung. Nurses are expected to be able to improve services in providing nursing care to pediatric patients, especially preschool age pediatric patients. AbstrakBerobat di rumah sakit (hospitalisasi) merupakan pengalaman yang tidakmenyenangkan dan mengancam bagi setiaporang,terutama bagi anak – anak yang masih dalam proses tumbuh kembang. Salah satu cara untuk mengatasi masalah tersebut adalah dengan menggunakan komunikasi terapeutik secara efektif yang akan dilakukan tindakan keperawatan. Untuk berkomunikasi dengan anak diperlukan pendekatan atau teknik khusus agar hubungan dapat berjalan dengan baik sesuai dengan tumbuh kembang anak. Salah satu faktor predisposisi menurut teori Lawrence Green adalah pengetahuan, bila perawat memiliki pengetahuan yang baik maka kemampuannya dalam komunikasi terapeutik juga akan baik. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan dengan keterampilan komunikasi terapeutik perawat pada pasien anak. Penelitian ini menggunakan metode survey analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah 66 perawat ruang rawat inap Rumah Sakit Graha Husada dengan teknik pengambilan sampel purposive sampling. Analisis data menggunakan uji korelasi Spearman Rank (Rho) dengan tingkat signifikansi (α = 0.05) diperoleh dari niai p 0.025 (p<0.05). Ada hubungan pengetahuan dengan kemampuan komunikasi terapeutik perawat pada pasien anak yang di rawat di RS Graha Husada Bandar almpung. Perawat diharapkan mampu meningkatkan pelayanan dalam memberikan asuhan keperawatan kepada pasien anak khususnya pasien anak usia prasekolah.